Hidróxido misto de níquel e manganês estabilizado na fase alfa: material promissor para dispositivos eletroquímicos de armazenamento de energia - Gomes, Allan Pablo (2019)
In the search for new energy resources, nickel hydroxide (Ni(OH) 2 ) has been widely studied as a positive electrode for secondary batteries, however, one of the limitations of this material is the rapid conversion between its polymorphic phases, affecting its electrochemical performance and, therefore, commercial applications. In order to stabilize Ni(OH) 2 on the polymorphic phase alpha, as well as to improve its electrochemical behavior, Ni 2+ ions were isomorphically replaced by Mn 2+ ions in different proportions (5, 25 and 50%) in Ni(OH) 2 . The mixed nickel and manganese hydroxides obtained by the modified Tower method presented nanometric dimensions (5 - 10 nm) confirmed by the transmission electron microscopy technique. Through the x-ray photoelectron spectroscopy technique it was possible to determine that the metal ions of the mixed hydroxides are in the 2+ oxidation state. All the mixed hydroxides synthesized showed the diffraction peak (003) at 2θ = 10.6o, thus confirming the alpha polymorphic phase. The electrochemical behavior of the modified electrodes was evaluated by cyclic voltammetry and electrochemical impedance spectroscopy. Even after 1000 voltammetric cycles the electrodes modified with the mixed hydroxides (Ni-75 and Ni-50) did not present a significant displacement of the anodic peak potential to more positive potentials, thus indicating the stabilization of the material in the alpha polymorphic phase. With the increase in the isomorphic substitution of Ni 2+ ions by Mn 2+ ions, a decrease in Ni 2+ / Ni 3+ charge transfer resistance wasobserved, as well as a significant increase in charge transfer re sistance for the evolution of O 2 . After 5000 consecutive charge and discharge cycles, electrodes modified with mixed hydroxides had a specific capacity of 187.5 C g -1 (Ni-95), 417.5 C g -1 (Ni-75) and 294.5 C g -1 (Ni-50) and a load retention of 90.6% (Ni-95), 86.5% (Ni 75) and 71.4% (Ni-50), these values being higher than the hydroxide of pure nickel and in summary are quite promising for the application in energy storage devices.